Access to finance and firm performance: Evidence from African countries - Babajide Fowowe (Review of Development Finance, 2017)
This study conducts an empirical investigation of the effects of access to finance on the growth of firms in African countries. In order to achieve this, we made use of a new rich enterprise-level data set from the World Bank's Enterprise Surveys and employ both subjective and objective measures of access to finance. The subjective measure of access to finance is obtained from the ranking of access to finance as no obstacle or severe obstacle to business operations. The objective measure of access to finance is a variable which measures whether firms are constrained in obtaining credit or not. We use data for 10,888 firms across 30 African countries and the results using the subjective measure show that the access to finance constraint exerts a significant negative effect on firm growth. Also, the results using the objective measure show that firms that are not credit constrained experience faster growth than firms which are credit constrained. These results lend credence to the view that financing is very important for firm growth, and justifies the many measures and initiatives being put in place to make more finance available for African firms.
Keywords: G10; G20; L25; O16; 650; Access to finance; Firm growth; Financial constraints; Africa